Aspects of Hanse archaeology in the Faroe Islands (AmS-Skrifter, 2020)
Compared to the neighbouring countries in the North Atlantic, very few sites in the Faroe Islands can be interpreted as trading sites ascribed to German merchants. This paper deals with physical evidence found around the islands that might attest to such activity. It is based on place-name evidence, local oral traditions, and, not least, archaeological remains, such as buildings and artefacts. A few sites are examined, and the presence of the Germans in the capital of Tórshavn is particularly discussed. Two of the most characteristic buildings at the peninsula of Tinganes, the Munkastovan and Leigubúðin, are reinterpreted. The site of Krambatangi on the island of Suðuroy is equally important for this discussion. Archaeological investigations took place there in 1952. The place-name as well as local tradition connected to the site suggest the presence of a merchants’ booth – a trading site – located by a very fine natural harbour. The site is located close to the local assembly site in the village of Øravík.